Spontaneous remission in primary membranous nephropathy: mechanisms, predictive factors, and implications for personalized management - Wu, Mengqi; Chen, Yanhao; He, Zixin; Jin, Youping (Frontiers in Immunology, 2025)
Primary membranous nephropathy (PMN) is a major cause of adult nephrotic syndrome and demonstrates considerable clinical heterogeneity. This review summarizes current evidence on the immunological mechanisms and clinical predictors underlying spontaneous remission (SR) in PMN. We discuss key factors including the dynamics of anti-PLA2R antibodies, proteinuria trends, renal function indicators, histopathological features, and emerging biomarkers. A staged immune modulation process is proposed, involving suppression of autoreactive responses and promotion of tissue repair. Integrating these insights, we also outline a personalized treatment approach based on dynamic risk stratification and longitudinal monitoring. Understanding the drivers of SR may help reduce unnecessary immunosuppression and guide precision management in PMN.